Clinical profile and outcome of adult Hodgkin lymphoma: Experience from a tertiary care institution - Maddi, Rahul Narayan; Linga, Vijay Gandhi; Iyer, Kalpathi Krishnamani; Chowdary, Joseph Stalin; Gundeti, Sadashivudu; Digumarti, Raghunadharao; Paul, Tara Roshini (Indian Journal of Medical and Paediatric Oncology, 2015)
Treatment and outcome of Hodgkin lymphoma (HL) are the true success story of modern medicine. The data from the developing countries on long-term outcome of patients with HL is sparse. Aims: Primary objective is to assess the progression-free survival (PFS). Secondary objective are overall survival (OS) and toxicities. Settings and Design: This is a retrospective analysis from the case records from a single institution. Materials and Methods: Institutional Ethical Committee approval was obtained. Between January 1991 and December 2010, 301 patients (age ≥18 years) underwent treatment at our institution. Statistical Analysis: Kaplan-Meyer curves were used to calculate the PFS and OS. Results: The median age at presentation was 36 years, range from 19 to 75 years. The male to female ratio was 2.9:1. Seventy-five percent of patients had B symptoms. Majority presented in advanced stage (Stage III and IV) disease (64.7%). Mixed cellularity (74.4%) was the most common histology, followed by nodular sclerosis (13.9%). The most common chemotherapy regimen used was ABVD (61%). Conclusions: Median follow-up of the cohort was 18.5 months (range 2-225). PFS and OS rate at 5 years is 66.3% and 79.7% respectively.
Keywords: Chemotherapy and toxicities; Hodgkin lymphoma; survival